2013
DOI: 10.1212/cpj.0b013e31828d9f2c
|View full text |Cite
|
Sign up to set email alerts
|

Value of thyroid and rheumatologic studies in the evaluation of peripheral neuropathy

Abstract: SummaryPeripheral neuropathy is a common disorder, often prompting an extensive initial laboratory evaluation. The initial evaluation is particularly challenging to primary care physicians and neurologists because of the broad differential diagnosis. Although screening thyroid and rheumatologic tests are frequently ordered, the diagnostic yield of these tests is unclear. Data from our institution were collected on patient demographics, clinical characteristics including warning signs suggestive of a diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…Of note, fewer than half of patients with SS-associated painful neuropathy are SS-seropositive [56], thus the actual prevalence of Sjögren’s syndrome is even higher. However, the 28% prevalence of high ESR here is comparable to the 22.3% prevalence identified in an older, male-predominant Michigan cohort [22]. …”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Of note, fewer than half of patients with SS-associated painful neuropathy are SS-seropositive [56], thus the actual prevalence of Sjögren’s syndrome is even higher. However, the 28% prevalence of high ESR here is comparable to the 22.3% prevalence identified in an older, male-predominant Michigan cohort [22]. …”
Section: Discussionsupporting
confidence: 56%
“…Serologic markers for all 3 conditions were far more often abnormal in the MGH cohort than in the population (Table 2), further evidence linking these conditions to SFPN and suggesting that some cases of iiSFPN are immune mediated. The current study reported the highest prevalence of ANA ≥ 1:160 (27.5%), with other surveys reporting 11% [50], 12.6% [22], and 4.6%. [60].…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations